2022
DOI: 10.1088/1757-899x/1234/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of elastomer: Case study – Rolling resistances of pneumatic and solid tyres

Abstract: EU tyre labelling rules have been applied since November 1st, 2012, to inform about the performances of tyres on fuel efficiency (rolling resistance), safety (braking on wet surfaces) and noise (external noise). The tyre labels help customers to make their purchase decisions by trade off on tyre performances and prices. Consequently, manufacturers have to engineer their products so that their tyres are classified on top of the label categories. Tyre rolling resistance involves in many kinds of tyre knowledge s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The tread pattern of the tire was neglected, as the research of Zeng et al [19] has shown that the thread profile only causes a constant offset in the displacement. The effect of threads on other mechanical properties of solid rubber tires was also considered to be minor [20]. It has to be noted that, while these parameters are partially hypothetical, the aim of the research is not to model the interaction of a specific vehicle and terrain, but to compare modeling methods.…”
Section: Parameters Of the Vehicle And Terrainmentioning
confidence: 99%
“…The tread pattern of the tire was neglected, as the research of Zeng et al [19] has shown that the thread profile only causes a constant offset in the displacement. The effect of threads on other mechanical properties of solid rubber tires was also considered to be minor [20]. It has to be noted that, while these parameters are partially hypothetical, the aim of the research is not to model the interaction of a specific vehicle and terrain, but to compare modeling methods.…”
Section: Parameters Of the Vehicle And Terrainmentioning
confidence: 99%
“…Tire labeling labels motor vehicle tire products that have met specific rolling resistance, wet grip, and noise emission requirements. This rolling resistance influence the vehicle's fuel consumption [1][2][3][4]. Therefore, reducing the rolling resistance of tires could contribute significantly to the energy efficiency of road transport and thus reduce emissions [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%